2015
DOI: 10.1002/cre2.9
|View full text |Cite
|
Sign up to set email alerts
|

Fit of cobalt–chromium implant frameworks before and after ceramic veneering in comparison with CNC‐milled titanium frameworks

Abstract: Computer‐aided design/computer‐aided manufacturing fabrication of implant‐supported frameworks is a standard procedure, and the use of ceramic‐veneered cobalt–chromium alloys is increasing. However, no data are available concerning the precision of fit of these frameworks and the impact on the fit of the veneering procedure. The aim of this study was to evaluate the fit of computer numeric‐controlled‐milled cobalt–chromium and titanium implant frameworks for edentulous maxillas, provided with six implants. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Results below 10 µm were also found in the literature for fixed prostheses prepared by CAD/CAM in zirconia, 12 titanium, and Co-Cr. 11 In the present study, after mechanical loading, the abutments in the TI, MM, and AM groups showed similar adaptation values, and all were within the same range as those reported in the literature for external hexagon implant abutments. 37,39 Metal abutments made by CAD/CAM systems using subtractive milling techniques appear to be highly accurate.…”
Section: Discussionsupporting
confidence: 89%
“…Results below 10 µm were also found in the literature for fixed prostheses prepared by CAD/CAM in zirconia, 12 titanium, and Co-Cr. 11 In the present study, after mechanical loading, the abutments in the TI, MM, and AM groups showed similar adaptation values, and all were within the same range as those reported in the literature for external hexagon implant abutments. 37,39 Metal abutments made by CAD/CAM systems using subtractive milling techniques appear to be highly accurate.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, CAD/CAM frameworks retained by implants improved the palatal obturator stability and functional results for patients with partial maxillectomy [ 11 ]. Titanium and cobalt-chromium alloys represent standard materials for CAD/CAM frameworks, with good performance and similar fit [ 12 ], while polyetheretherketone (PEEK) is an inert, non-allergenic polymeric biomaterial, indicated as a substitute for metal alloys in assorted types of prostheses and orthoses, including craniofacial prostheses [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…(19) This result was in agreement with that of Tiossi et al (30) who compared titanium and Co-Cr frameworks in three-unit implant retained FDPs before and after simulated porcelain firings and reported insignificant differences. Controversy, Svanborg et al (20) found that ceramic veneering resulted in minor improvement of the fit for Co-Cr full arch implant supported frameworks, the difference in the results may be attributed to the difference in the restoration type as they used full arch Co-Cr and CNC milled Ti frameworks. On the other hand, Kaleli and Saraç (21) reported that marginal discrepancy increased after porcelain application for metal ceramic restorations with Co-Cr frameworks prepared by different methods.…”
Section: Discussionmentioning
confidence: 99%
“…(18) Several studies have reported that the porcelain firing stages affect the fit of the Co-Cr restorations. (11,(19)(20)(21) Another crucial factors for the long term success of implant supported metal ceramic restoration are their mechanical resistance and structural integrity in the oral cavity. (2) The mechanical response of the functionally loaded metal ceramic restoration is dependent on the mechanical properties of the supporting metal core which rely on material composition and production method.…”
Section: Introductionmentioning
confidence: 99%